Design and evaluation of metal-liganded bioactive delivery system for enhanced oral bioavailability - M'bitsi-Ibouily, Gretta (My University, 2019)
The oral delivery of drugs, especially solid formulations, is one of the most common and widely used routes of drug administration, accounting for approximately 50% of all dosage forms currently on the market. Nevertheless, oral drug delivery of poorly soluble and permeable drugs can be particularly challenging, resulting in low bioavailability and high dosages of these drugs. Consequently, patient compliance is reduced, thereby negatively affecting the intended therapeutic intervention. The preference of patients for the oral route is particularly true in chronic drug therapy, as is the case in the treatment of schizophrenia, due to its convenience and non-invasiveness. Schizophrenia is a severe and incapacitating mental disorder with serious consequences if not properly treated. Sulpiride (SPR) is an antipsychotic agent with proven efficacy in reducing both the positive and negative symptoms of schizophrenia. However, this drug displays various pharmacokinetic limitations including poor aqueous solubility, limited permeability, burst drug release, short half-life and low bioavailability. Sulpiride therapy therefore requires large doses to reach therapeutic efficacy and hence multiple drug administrations. As a result of such therapy regimen, undesirable side effects are experienced and patient compliance is compromised, which ultimately results in lower clinical outcomes. This study reports the design, formulation, characterization and evaluation of a Metal Complex Polymer Nanocomposite (MCPN) delivery system for the sustained oral delivery of sulpiride. A transition metal organometallic complex of ruthenium (Ru) was designed using Ru as an inert drug carrier complexed to sulpiride to obtain a metal-liganded bioactive, [Ru(p -cymene)((R)-(+)-2-amino-3-phenyl-1-propanol)(SPR)]PF6. A series of analogues were thus designed, synthesized and characterized employing elemental analysis, Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance (NMR), thermal analyses and Ultraviolet-Visible (UV-Vis). The metal-liganded bioactive was then evaluated for solubility of SPR in different solvents, ex vivo permeation of SPR through porcine intestine, and in vitro release of SPR in different pH environments. SPR liganded to the metal exhibited enhanced aqueous solubility (1668 mg/L ± 1.38) and intestinal relative permeability (27.20%) but burst drug release was still observed in vitro. The obtained metal-liganded bioactive was then encapsulated into polymeric nanoparticles using Eudragit® RS 100 and polyvinyl alcohol (PVA) to obtain the MCPN delivery system. The biodegradable copolymer Eudragit® RS 100 was used to protect the metal-liganded bioactive from bond cleavage in gastric pH and provide sustained drug release, while the water-soluble synthetic polymer PVA was used as the aqueous phase for nanoparticle production and to maintain sustained drug release. The designed MCPN was synthesized and evaluated for particle size, zeta potential, entrapment efficiency and drug loading. Further characterization included Differential Scanning Calorimetry (DSC), FTIR and Scanning Electron Microscopy (SEM). The MCPN was then evaluated for ex vivo permeation of SPR through porcine intestine, in vitro release of SPR in simulated gastric, intestinal and systemic circulation environments. The Taguchi design method with L9 orthogonal array was used to optimize the MCPN formulation. The optimized MCPN formulation was evaluated for in vitro toxicity in Caco-2 cell line. SPR in optimized MCPN (particle size: 92.77±3.96, zeta potential: -32.23±3.07, entrapment efficiency: 87.82% and drug loading: 27.45%) resulted in improved intestinal relative permeability (75.65%) and a sustained in vitro drug release profile orally, with no noticeable toxic effects on the intestinal epithelium tissue. The in vivo study involved the oral administration of conventional capsule and MCPN capsule to pigs for a comparative study of the two formulations and the collection of blood samples at specified time points for the quantification of SPR and Ru in the animals’ plasma using Ultra Performance Liquid Chromatography (UPLC) and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS), respectively. Pharmacokinetic modelling determined sulpiride release, that was best described by a non-compartmental model. The MCPN capsule exhibited a higher SPR peak plasma concentration (Cmax = 0.9895 μg/mL), reached at an increased time (tmax = 12 hours) compared to the conventional capsule (Cmax = 0.8719 μg/mL and tmax = 6 hours). The MCPN delivery system improved the bioavailability of SPR by 25.04% (from 30.26% for the conventional capsule to 55.30% for the MCPN capsule). A Level-A in vitro-in vivo correlation was developed that detailed a 79% predictability of sulpiride release. The quantification of Ru in the plasma, liver and kidneys of each pig after MCPN capsule administration using ICP-MS revealed no hematologic, hepatic or renal toxicity associated to the presence of Ru in the MCPN delivery system. The MCPN delivery system provided enhanced bioavailability of SPR through SPR gastric pH protection, improved SPR aqueous solubility, enhanced intestinal permeability (lipid solubility) and reduced particle size of the formulation. Finally, the MCPN exhibited sustained release of SPR, which allows for maintained therapeutic concentrations of the drug in the systemic circulation throughout the dosing interval, resulting in a lower dosage, reduced side-effects and ultimately improved patient compliance. The combination of metal complexation and nanotechnology was successful in improving the oral bioavailability of sulpiride.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2019